2014
DOI: 10.1186/1756-3305-7-13
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study on gastrointestinal nematodes from two Swedish cattle farms showing field evidence of ivermectin resistance

Abstract: BackgroundAnthelmintic resistance (AR) is an increasing problem for the ruminant livestock sector worldwide. However, the extent of the problem is still relatively unknown, especially for parasitic nematodes of cattle. The effect of ivermectin (IVM) (Ivomec inj.®, Merial) was investigated in Swedish isolates of gastrointestinal nematode (GIN) populations showing signs of AR in the field to further characterise the AR status by a range of in vivo and in vitro methods.MethodsThree groups, each of 11 calves, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…Furthermore, those authors found that L3 both susceptible and resistant to anthelmintics showed increased expression of Con-pgp11, Con-pgp12, Con-pgp16 and Con-mrp1 after in vitro exposure to ML [15]. Con-pgp9 was included because increased expression of this gene has been reported in C. oncophora surviving ML treatment [5]. In addition, increased expression of P-gp9 has been reported in ML resistant T. circumcincta and H. contortus [12,13].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, those authors found that L3 both susceptible and resistant to anthelmintics showed increased expression of Con-pgp11, Con-pgp12, Con-pgp16 and Con-mrp1 after in vitro exposure to ML [15]. Con-pgp9 was included because increased expression of this gene has been reported in C. oncophora surviving ML treatment [5]. In addition, increased expression of P-gp9 has been reported in ML resistant T. circumcincta and H. contortus [12,13].…”
Section: Discussionmentioning
confidence: 94%
“…After patency, adult worms were collected at necropsy from one animal 4 days before treatment and from another animal 10 days after subcutaneous injection of the calves with IVM (Ivomec ® vet, 0.2 mg per kg), as described by Areskog et al [5].…”
Section: Laboratory-selected Isolatementioning
confidence: 99%
See 1 more Smart Citation
“…Another case of IVM resistance in T. circumcincta populations was suspected in the present study in one farm with a fecal egg count reduction of 84%. However, in absence of an IVM-controlled efficacy test using animals experimentally infected with the Bputativer esistant strain, pharmacokinetic analyses, and post-mortem examinations after treatment, the results obtained in the present study should be taken carefully as some discrepancies have been reported between FECR tests obtained with naturally grazing animals in one hand and experimentally infected animals in the other (Areskog et al 2013). If demonstrated, the Bmultiple^resistance detected in farm B may either be due to the presence of sub-populations of parasites that are monoresistant, i.e., only resistant to a single class of anthelmintic or by the presence of parasites carrying resistance to multiple anthelmintic drugs.…”
Section: Discussionmentioning
confidence: 91%
“…Parasites acquire their food from their hosts, causing poor health and stress in the host organism that leads to an increased vulnerability to other diseases. The widespread emergence of anthelminticresistant strains of the highly pathogenic parasitic nematode Haemonchus contortus and other economically important parasites has resulted in the need to develop unconventional control strategies 2 . H. contortus and Ostertagia ostertagi are mostly pathogenic to sheep and cause effects ranging from mild anaemia to mortality in young animals because of their blood-feeding behaviour.…”
mentioning
confidence: 99%